3449 Bacterial biotransformation of chemotherapeutics may promote diversity among the intestinal microbiota - Ryan Andrew Blaustein; Patrick Casey Seed; Erica Marie Hartmann (Journal of Clinical and Translational Science, 2019)
OBJECTIVES/SPECIFIC AIMS: This study aims to test the hypothesis that bacterial biotransformation of chemotherapeutics promotes gut microbial diversity by enhancing persistence of drug-sensitive taxa. METHODS/STUDY POPULATION: The impacts of doxorubicin on a model community of gut bacteria was investigated in vitro in anaerobic batch culture. The synthetic community was composed of specific members predicted by genomic analysis to be sensitive to the therapeutic (i.e., Clostridium innocuum, Lactobacillus sp.), resistant via putative biotransformation (i.e., Escherichia coli, Klebsiella pneumoniae), or resistant via putative efflux (i.e., Enterococcus faecalis). Bacterial growth was monitored in monocultures by measuring OD600 and standard plate counts, and in mixed cultures by strain-targeted qPCR. Doxorubicin concentration was detected via absorbance assay. RESULTS/ANTICIPATED RESULTS: Strains with predicted resistance to doxorubicin by drug biotransformation significantly lowered concentrations of the drug in culture media. In contrast, E. faecalis proved resistant without evidence of drug transformation. Predicted sensitive strains were growth-repressed by the doxorubicin, but able to grow in spent media where biotransformation had occurred. However, they remained growth-repressed in spent media from E. faecalis where drug transformation had not been observed. Bacterial growth kinetics in mixed batch culture were dependent on starting bacterial concentrations and timing of drug exposure. DISCUSSION/SIGNIFICANCE OF IMPACT: This work will be extended to model microbial community responses to doxorubicin as a factor of microbial interactions and extent of drug transformation prior its exposure to sensitive strains. The resulting model will have translational implications for mitigating health risks during pediatric cancer treatment.